Advertising across cultures, where translation is nothing… or everything - Cruz Garcia, Laura (The Journal of Specialised Translation, 2018)
This article deals with the concept of 'translation' in the field of advertising, often known as 'copy adaptation.' The different advertising strategies used when adverts are published or broadcast in different countries involve different approaches to the task and the study of translation in this context. Standardisation (or globalisation) and localisation (or adaptation), two opposing advertising strategies, require different translation procedures. The main purpose of this paper is to examine the extent to which what is termed 'advertising translation' can actually be considered to be translation or not, bearing in mind existing definitions of translation and classifications of translation strategies. To this end, definitions of 'translation' from different periods of time (paradigms) will be observed, with an emphasis on the evolution that this concept, and corresponding term, has undergone as it has gradually incorporated different text types and specific translation activities. To illustrate the dynamic nature of this field of study, we will present and analyse pairs of advertisements (comprising an original advert and its translated version) in the translation of which specific strategies or solutions regarding the transfer of the message have been used. In the course of this study, a key question is posed: is adaptation different from translation or is it part of translation? The conclusion shows that transfers in advertising largely depend on functionalist strategies of translation, and therefore on translation in general.